Radicalization as a Pathway to Asymmetric Warfare: A Historical Study of the Abu Sayyaf Group in Southern Philippines - Joshua Insetyadi B; Muhammad Halkis; Agus Hasan Sulistiyono Reksoprodjo (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The relationship between radicalization and asymmetric warfare remains insufficiently explained in historically grounded analyses of non-state armed groups. This study examines radicalization as a pathway to asymmetric warfare through a historical analysis of the Abu Sayyaf Group (ASG) in the Southern Philippines. Employing a qualitative literature-based approach, the study draws on academic books, peer-reviewed journal articles, research reports, and official documents addressing the Moro conflict, ASG’s historical development, radicalization, terrorism, and asymmetric warfare. The data were examined through qualitative content analysis and historical process tracing, with Moghaddam’s Staircase to Terrorism serving as the primary analytical framework. The findings demonstrate that ASG’s development was embedded in a protracted historical context characterized by colonial legacies, political marginalization, socioeconomic disparities, land disputes, and perceived injustice. These conditions facilitated the emergence of radical narratives that were subsequently reinforced by Salafi-jihadist ideology, organizational recruitment, military training, and transnational connections. Radicalization also coincided with organizational and strategic transformation, as reflected in the increasing use of kidnapping, hostage-taking, bombing, ship hijacking, and criminal financing. Amid substantial military and organizational asymmetries between ASG and the Philippine state, these unconventional forms of violence provided the group with alternative means of confrontation. The study concludes that radicalization does not automatically produce asymmetric warfare; rather, it constitutes a pathway through which grievances are ideologically reframed, violence is legitimized, organizational capacity is developed, and unconventional strategies become viable for a weaker non-state actor. These findings contribute a historically grounded explanation of how radicalization processes can enable non-state armed groups to adopt asymmetric modes of warfare.